The Ex Vows - Joyce, Jessica (New York : Berkley Romance, 2024)
"Georgia Woodward lives by her lists, none more so than the one about her ex, Eli Mora. It's full of the ironclad dos and don'ts they've been following since she returned to the Bay Area after their cataclysmic breakup five years ago. With the wedding of their mutual best friend Adam looming, and them about to step into their roles as best woman and man, Georgia's never needed it more. She refuses to threaten their tight-knit friend group with her messy--and still very present--feelings. The rules on that list will keep her cool, calm, and compartmentalized. What's not on her list? Eli arriving from New York with a new rule-breaking attitude, or the all-inclusive venue burning to the ground, leaving the bride and groom in dire straits"--
Keywords: Lists -- Fiction; Weddings -- Fiction; Best friends -- Fiction; Love-hate relationships -- Fiction; Man-woman relationships -- Fiction; Romance fiction